Gamifikasi dalam Pendidikan Fisika: Tinjauan Konseptual Pemanfaatan Lembar Kerja Digital untuk Keterampilan Berfikir Kritis - Fitri Afnan; Nia Ulva Sari; Milya Sari; Raudhatul Jannah; Nurhasnah Nurhasnah (STKIP HARAPAN BIMA, 2026)
Digital transformation demands innovative physics learning media to improve students’ critical thinking skills, which remain low due to the dominance of conventional teaching methods. This study aims to identify effective gamification elements in supporting student engagement and the development of critical thinking skills through the use of gamification-based digital worksheets in physics learning. The method used was a literature review by analyzing relevant national and international journal articles published between 2021 and 2026. The literature search and selection process followed the PRISMA flow, including identification, removal of duplicates, screening based on titles and abstracts, full-text eligibility assessment, and inclusion of articles that met the research criteria. The results of the review indicate that this combination facilitates problem-solving activities that significantly contribute to the development of critical thinking skills and Higher Order Thinking Skills (HOTS). The integration of gamification elements such as points, badges, leaderboards, and challenges into interactive digital worksheets enhances students’ motivation, focus, and cognitive engagement. It is concluded that gamification-based digital worksheets are an effective alternative innovative learning medium for creating student-centered physics learning and meeting the demands of 21st-century skills.